(untitled) (African Journal of Biomedical Research, 2021)
Background: The increase in the development of cardiovascular disease (CVD) has led to more investigations of the pivotal components imperative in the prevention and treatment of CVD. Analysis of lipid parameters with patient history has been crucial in risk classification of patients and monitoring treatment. However, there are patients with acute coronary events with normal lipid parameters and family history, which led to the interest in atherogenic LDL sub-fractions. Objective: The objective was to observe the lipid profile and LDL species of patients with hypertension, hypertensive heart disease (HHD) and those with acute coronary syndrome (ACS) Method: Plasma from 92 patients was analysed using gradient gel electrophoresis (GGE), serum was analysed for total cholesterol (TC), LDL-C, HDL-C and triglyceride (TG). A self-administered questionnaire was used to collect demographics and relevant histories. Results: A significantly low HDL-C concentration was observed across all patient groups (HTN p<0.001, HHD p<0.001, ACS p<0.001). Analysis of GGE images revealed that increased TG levels and low HDL-C levels associated with a predominance of LDL phenotype B. It was also observed that LDL-C levels exhibited no precipitating role in the development and progression from LDL phenotype A to I and B. Furthermore, not all patients with ACS had a predominance of LDL phenotype B. Conclusion: High TG levels displayed a causal role in the production of smaller LDL particles. The combination of low HDL-C and elevated TG levels were better indicators than the LDL-C level in association with the atherogenic LDL particles in assessment of CVD risk.